ANALISIS LAPORAN KEUANGAN DAN PROYEKSI ARUS KAS PDAM KOTA PONTIANAK TAHUN 2020-2023 - Syahbandi Syahbandi; Djunita Permata Indah (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2023)
Cash flow can be a very useful tool for companies in repairing and managing company assets, so it is necessary to calculate cash flow projections to ensure cash availability for the company. This study aims to calculate cash flow predictions at PDAM Pontianak City for 2020-2023 based on the 2017-2019 financial reports and compared with the actual profit (loss) reports for 2020-2021. The results of the study show that in predicting cash flows, there will be a very significant decrease if efforts to improve and manage assets are not carried out at this time. However, from 2020 to 2021, PDAM Tirta Khatulistiwa has succeeded in improving and managing assets so that they can increase company profits by keeping the value of operating expenses at a fairly stable number.